Aerobic post-processing of digestate from a multi-stage anaerobic digester - Sandefur, Julie N., author; Sharvelle, Sybil, advisor; De Long, Susan, committee member; Davis, Jessica, committee member (Colorado State University. Libraries, 2017)
The management of animal waste from feedlots is inconvenient and costly due to the storage and transportation involved in ensuring the waste is utilized appropriately. Anaerobic digestion is a proven method for breaking down waste with low solids content and capturing methane produced to use as renewable energy. Composting is an age-old process in which solid waste retains its nutrients and becomes a suitable, natural soil amendment. By combining these methods within multi-stage anaerobic digestion (MSAD), two valuable by-products are generated – methane and nutrient-laden compost – through a process able to handle high solids material. A laboratory-scale study was conducted to simulate aerobic composting of high solids cow manure (HSCM) in a leachate bed reactor (LBR) after anaerobic digestion from a MSAD. Analysis of the leachate and solid material were performed after each phase: anaerobic – 21 days, active aerobic – 21 days, and curing - 60 days. The effects of agricultural by-products used as bulking material in the LBRs and of compost inoculum added were also assessed. The bulking material assisted in providing uniform flow of leachate through the LBRs during the anaerobic phase and served as an additional carbon source once aeration began. Inoculum acquired from Colorado State University's (CSU) composter was added at the beginning of the aeration phase via two different methods alongside a control group in order to assess the potential contributions of including already composted organic material still containing active bacteria. Compost quality parameters monitored consisted of ammonium to nitrate ratio, carbon to nitrogen ratio, pH, soluble salts, sodium absorption ratio (SAR), percent total nitrogen, phosphorus, and potassium, and the Solvita® Maturity Index (SMI). There was a sizable volatile solids reduction (%VS) observed of the HSCM only in two of the three different bulking material reactor sequences. The bulking material study showed a 41% ± 0.12, 33% ± 0.03 and 55% average reduction in the manure for corn stover, beanstalk, and woodchip reactors respectively. The woodchips most likely contributed to the larger solids reduction due to their larger particle size and more rigid structure allowing leachate and air more pathways to access and breakdown material. VS reduction in the inoculum study showed that there was no solids reduction benefit achieved by including a 1:2 municipal solid waste (MSW)-horse manure combined inoculated compost to the reactors prior to the active aeration phase. The control reactors outperformed the reactors where inoculum was added on top or mixed in with the digestate. The quality of the matured compost from all the reactors in both studies met or exceeded required specifications. The stability and maturity of the composts were compared to Rocky Mountain Region Classification tables as well as the SMI range. In each case, the analytes measured were below the suggested limits in the classification table and most fell in the "finished compost" range on the SMI scale. The values of the major nutrients assessed were of satisfactory contents as to be useful for land application. This study seeks to encourage the process of MSAD on feedlots with HSCM in arid to semi-arid regions by demonstrating the usefulness of the by-products achieved from the process. Methane gas produced in the anaerobic phase is a valuable form of renewable energy that can be used onsite. A mature compost product meeting Class 1 Compost/ Soil Amendment Classification standards can be used onsite or sold for a variety of applications. By generating methane and beginning the composting process in the same LBR, solids are further reduced, weight is minimized and the material is more stable for transportation and storage.
Keywords: bulking material; cow manure; volatile solids; composting; anaerobic digestion; inoculum